KORELASI ANTARA KEMANDIRIAN BELAJAR SISWA DAN MEDIA PEMBELAJARAN DENGAN HASIL BELAJAR IPA SISWA KELAS VIII SMPN 8 PEKANBARU - Gusni Mulyani; Darmawati Darmawati; Arnentis Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Research has been conducted at Pekanbaru SMP N 8 in April to November 2018 which aims to determine the correlation between student learning independence and learning media with the science learning outcomes of class VIII students at Pekanbaru 8 Junior High School using purposive sampling technique. The sample used in this study was students of class VIII-5, amounting to 30 students. The variables observed in this study were student learning independence and learning media and the instruments used were learning independence questionnaires and learning media. Furthermore, the data were analyzed by Spearman rank correlation analysis at the level of 5% using the SPSS application and descriptive analysis was carried out. The results of the analysis of learning independence and learning media have a correlation at a significant level of 5% with student learning outcomes. Learning independence has a correlation of 0.765 with learning outcomes and learning media has a correlation of 0.728 with learning outcomes. Based on the results of the study it can be concluded that there is a strong correlation between learning independence and learning media with science learning outcomes which is equal to 0.798.Keywords: Correlation, Learning Independence, Learning Media, Learning Outcomes